Radiofrequency ablation of hyperplasia at an uncovered portion of a partially covered metal stent in endoscopic ultrasound‐guided hepaticogastrostomy (with video). (8th July 2021) - Matsubara, Saburo; Nakagawa, Keito; Suda, Kentaro; Fujita, Tetsuro; Otsuka, Takeshi; Oka, Masashi; Nagoshi, Sumiko
Abstract : Highlight Endoscopic ultrasound‐guided hepaticogastrostomy with a partially covered metal stent has a potential risk of stent occlusion due to hyperplasia at an uncovered portion of the stent. Matsubara and colleagues report that radiofrequency ablation of hyperplasia with additional placement of an uncovered metal stent is useful for preventing recurrent stent occlusion.